Acid ceramidase targeting pyruvate kinase affected trypsinogen activation in acute pancreatitis - Juan Xiao; Wenying Zeng; Pengcheng Zhang; Yuan Zhou; Qiangqiang Fang (BMC, 2022)
Abstract Background Acute pancreatitis is the sudden inflammation of the pancreas. Severe cases of acute pancreatitis are potentially fatal and have no specific treatment available. Premature trypsinogen activation could initiate acute pancreatitis. However, the mechanism underlying premature trypsinogen activation is not fully understood. Methods In this research, a primary pancreatic acinar cell or mouse acute pancreatitis model was constructed. The effect of acid ceramidase (ASAH1), which is responsible for sphingosine production, was investigated in trypsinogen activation in vitro and in vivo. Meanwhile, the proteins regulating ASAH1 or binding to sphingosine were also detected by co-immunoprecipitation followed by mass spectrometry. Results The results showed that ASAH1 increased in acute pancreatitis. Increased ASAH1 promoted the activation of trypsinogen and cathepsin B. On the contrary, ASAH1 downregulation inhibited trypsinogen and cathepsin B. Meanwhile, ASAH1 regulated the activity of trypsin and cathepsin B through sphingosine. Additionally, E3 ligase Mind bomb homolog 1 (MIB1) decreased in acute pancreatitis resulting in the decreased binding between MIB1 and ASAH1. Exogenous MIB1 diminished the elevation in trypsin activity induced by acute pancreatitis inducer. ASAH1 increased owing to the inhibition of the proteasome degradation by MIB1. In acute pancreatitis, sphingosine was found to bind to pyruvate kinase. Pyruvate kinase activation could reduce trypsinogen activation and mitochondrial reactive oxygen species (ROS) production induced by sphingosine. Conclusions In conclusion, during the process of acute pancreatitis, MIB1 downregulation led to ASAH1 upregulation, resulting in pyruvate kinase inhibition, followed by trypsinogen activation.